Policy of the Degree Course in Philosophy of UFT: challenges for the management of the training of entering students in ideal time - Roberto Francisco de Carvalho; Mariana Aparecida Aranha; Doracy Dias Aguiar de Carvalho (Universidade Federal do Norte do Tocantins, 2023)
This article aimed to diagnose the number of entering students who complete, in the ideal period, the Degree Course in Philosophy Campus of Palmas / UFT through the study of performance reports extracted from SIE/UFT. This is a bibliographic and documentary study that allowed us to observe that the teacher training courses of Brazilian public universities have, to a large extent, responded to the economic-mercantilist logic, which also impacts the teaching training process within the scope of UFT. In the case of the Course studied, the data show that most students do not graduate in the ideal time or in the maximum time allowed, in addition to the fact that most of the entering students drop out of the course before its completion.